Antifungal Compounds Produced by Colletotrichum gloeosporioides, an Endophytic Fungus from Michelia champaca - Chapla, Vanessa Mara [UNESP]; Zeraik, Maria Luiza [UNESP]; Leptokarydis, Ioanis Hcristos [UNESP]; Silva, Geraldo Humberto; Bolzani, Vanderlan da Silva [UNESP]; Young, Maria Claudia M.; Pfenning, Ludwig Heinrich; Araújo, Angela Regina [UNESP] (Mdpi Ag, 2014)
In this study, eight endophytic fungi were isolated from the leaves, stems and roots of Michelia champaca. The isolates were screened and evaluated for their antifungal, anticancer and acetylcholinesterase (AChE) inhibitory activities. All of the extracts exhibited potent activity against two evaluated phytopathogenic fungi. Chemical investigation of EtOAc extracts of the endophytic fungus Colletotrichum gloeosporioides resulted in the isolation of one new compound, 2-phenylethyl 1H-indol-3-yl-acetate (1), and seven known compounds: uracil (2), cyclo-(S*-Pro-S*-Tyr) (3), cyclo-(S*-Pro-S*-Val) (4), 2(2-aminophenyl)acetic acid (5), 2(4-hydroxyphenyl) acetic acid (6), 4-hydroxy-benzamide (7) and 2(2-hydroxyphenyl) acetic acid (8). All of the compound structures were elucidated using 1D and 2D NMR and MS analyses. The antifungal and AChE inhibitory activities of compounds 1-8 were evaluated in vitro. Compound 1 exhibited promising activity against Cladosporium cladosporioides and C. sphaerospermum that was comparable to that of the positive control nystatin.
Keywords: Colletotrichum gloeosporioides; endophytic fungus; antifungal activity